Perancangan Interior K-Pop Experience Center di Surabaya - Dewi, Savitri Kartika; Yong, Sherly de; Kayogi, David Tan (Intra, 2019)
Korean Wave, called Hallyu in Korean, is a pop-culture phenomenon from South Korea spread globally. In Indonesia, especially Surabaya, there are numerous K-Pop fans. A facility based on K-Pop experience center in Surabaya is needed to accomodate the fans appreciative activities also inform and present new experiences based on educative, interactive, and recreative values. Design Thinking method was used as design guideline with the steps of Define, Research, Ideate, Prototype, Selection, Implementation, and Learn. The interior design will be implemented along with experience-based programÂ using latest technologies to reach the goal of the design.